Retrograde intramedullary nail fixation compared with fixed-angle plate fixation for fracture of the distal femur: the TrAFFix feasibility RCT. - Griffin, X; Costa, M; Phelps, E; Parsons, N; Dritsaki, M; Png, M; Achten, J; Tutton, E; Lerner, R; McGibbon, A; Baird, J (National Institute for Health Research, 2019)
BACKGROUND:Fractures of the distal femur are an increasingly common injury; the optimal management of these injuries remains controversial. The two interventions used in UK practice are intramedullary fixation, with a locked retrograde nail, and extramedullary fixation, with a fixed angle plate. OBJECTIVES:This study assessed the feasibility of a definitive trial and included a process evaluation to understand the generalisability and likely success of a future trial. DESIGN:A multicentre, parallel, two-arm, randomised controlled feasibility trial with an embedded process evaluation. Treatment with a plate or nail was allocated in a 1 : 1 ratio, stratified by centre and chronic cognitive impairment. Surgeons were not blinded, but participants were not told their allocation. SETTING:Seven NHS hospitals. PARTICIPANTS:Patients aged ≥ 18 years with a fracture of the distal femur who the attending surgeon believed would benefit from internal fixation were potentially eligible. Patients were excluded if they had a loose arthroplasty requiring revision or a femoral deformity or arthroplasty that precluded nail fixation. The sample was recruited between 29 September 2016 and 31 August 2017. Consent was obtained from the patient or appropriate consultee before enrolment. INTERVENTIONS:Patients were randomised to receive fixation of their distal femur fracture with either a proximally and distally locked retrograde nail that spanned the diaphysis of the femur or an anatomical distal femoral locking plate with at least one locked screw distal to the fracture. Reduction and supplemental fixation were at the surgeon's discretion. OUTCOMES:The primary outcome measures for this study were the recruitment rate and the completion rate of the EuroQol-5 Dimensions, five-level version (EQ-5D-5L), at 6 weeks and 4 months. Additional measurements included baseline characteristics, measures of social support and self-efficacy, disability rating index, dementia quality-of-life measures and a radiographical assessment of any malunion. Participants' and staff views were obtained, at interview, for the process evaluation. RESULTS:The process evaluation showed that surgeon-related factors, principally confidence with both technologies and a lack of individual equipoise, were key barriers to recruitment. A total of 23 participants were randomised and analysed (nail, n = 11; plate, n = 12). The recruitment rate was estimated as 0.42 [95% confidence interval (CI) 0.27 to 0.62] participants per centre per month, lower than the prespecified feasibility threshold of 1.0 participants per centre per month. Data completeness of the EQ-5D-5L was estimated at 65% (95% CI 43% to 83%). CONCLUSIONS:This feasibility study has challenged many of the assumptions that underpinned the development of proposed definitive trial protocol. A modified protocol is proposed that would be feasible given the recruitment rate observed here, which is equal to that reported in the similar FixDT trial [Health Technology Assessment (HTA) 11/136/04: Costa ML, Achten J, Hennings S, Boota N, Griffin J, Petrou S, et al. Intramedullary nail fixation versus locking plate fixation for adults with a fracture of the distal tibia: the UK FixDT RCT. Health Technol Assess 2018;22(25)], which delivered to target and budget. FUTURE WORK:A definitive trial with a modified design is recommended, including an internal pilot to confirm initial recruitment rate assumptions. REGISTRATION:Current Controlled Trials ISRCTN92089567. FUNDING:This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 23, No. 51. See the NIHR Journals Library website for further project information. Funding was also supported by the NIHR Oxford Biomedical Research Centre.